Portrait of Junior High School Students' Statistical Literacy through PISA on Uncertainty and Data Content - Satria Bayu Herlambang; Duano Sapta Nusantara; Feri Tiona Pasaribu (Faculty of Teacher Training and Education, 2025)
Statistical literacy is a critical 21st-century competency, as students increasingly encounter data-driven information in their everyday lives. However, international assessments such as PISA consistently show that Indonesian students struggle to interpret and reason with data. This study aims to investigate junior high school (JHS) students’ statistical literacy in solving PISA-based problems related to uncertainty and data, while also linking the results to Sustainable Development Goal (SDG) 4: Quality Education. A descriptive qualitative approach was employed involving 40 ninth-grade students from JHS Negeri 6 Kota Jambi, selected through purposive sampling to represent high, medium, and low academic ability groups. Data were collected through a validated PISA 2012 item focusing on uncertainty and data, along with semi-structured interviews designed to explore students’ statistical-literacy strategies. Data analysis followed an interactive model consisting of data reduction, data display, and conclusion drawing, guided by Schield’s (2011) statistical-literacy indicators. The findings indicate that only 17.5% of students demonstrated a high level of statistical literacy, while most were categorized as medium (37.5%) or low (45%). Further analysis revealed persistent difficulties in identifying trends, calculating averages, and drawing valid conclusions. These findings underscore the need for contextual, PISA-based learning tasks that foster statistical reasoning and strengthen students’ fundamental literacy skills as a foundation for achieving quality education.